Preparation of protoplasts and regeneration of intact cells of Streptomyces cinnamonensis - Jandová, Z; Tichý, P (Folia microbiologica, 1990)
Protoplasts were prepared and intact cells were regenerated in Streptomyces cinnamonensis--a monensin producer--to make genetic manipulations with this strain possible. 70-80% of protoplasts were formed and up to 90% of them could regenerate into intact cells.
Keywords: Protoplasts; protoplasty; Streptomyces; kultivační média; Culture Media